2022
DOI: 10.3389/fnut.2022.1056445
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic prospects of dietary bio-actives of millets and the significance of the gut microbiota: A case of finger millet

Abstract: Finger millet (Eleusine coracana) is a staple food in several parts of the world because of its high nutritional value. In addition to its high nutrient content, finger millet contains numerous bioactive compounds, including polyphenol (10.2 mg/g TAE), flavonoid (5.54 mg/g CE), phytic acid (0.48%), and dietary fiber (15–20%). Polyphenols are known for their anti-oxidant and anti-diabetic role. Phytic acid, previously considered an anti-nutritive substance, is now regarded as a nutraceutical as it reduces carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…Lactobacillus is widely regarded as a beneficial bacterium that helps maintain a healthy balance of gut microbiota and prevents the invasion of pathogens ( Angelakis and Raoult, 2010 ). Eubacterium has a significant role in reducing systemic inflammation by preserving the integrity of the gut barrier and preventing the invasion of pathogenic microbes and toxins ( Singh et al, 2022 ). Coprococcus , on the other hand, is an important produce of butyrate, which plays a role in evaluating the gastrointestinal tract’s health as a microbial biomarker ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus is widely regarded as a beneficial bacterium that helps maintain a healthy balance of gut microbiota and prevents the invasion of pathogens ( Angelakis and Raoult, 2010 ). Eubacterium has a significant role in reducing systemic inflammation by preserving the integrity of the gut barrier and preventing the invasion of pathogenic microbes and toxins ( Singh et al, 2022 ). Coprococcus , on the other hand, is an important produce of butyrate, which plays a role in evaluating the gastrointestinal tract’s health as a microbial biomarker ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a balanced calcium dietary intake is recommended because excessive calcium is linked with mortality and causes vascular events in people receiving calcium supplementation [ 28 , 29 ]. The prebiotic components inherent in millets are metabolized by indigenous bacteria in the human gut to produce beneficial short-chain fatty acids and probiotics from the colon, which have been shown to possess antidiabetic properties [ 30 ]. Foxtail millet is particularly rich in resistant starch, which has the ability to delay gastric emptying and decrease post-consumption blood glucose levels [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…a small study in Mali found that thick porridges and couscous made from millet took twice as long to digest than similar products made from rice, potato or pasta, leaving study participants more satisfied. (12) Millet's slow digestibility is attributed to its high resistant starch and fibre content (13).…”
Section: Studiesmentioning
confidence: 99%